PERANCANGAN BUKU ILUSTRASI DIGITAL PANDUAN PEMBUATAN BIOPESTISIDA DARI DAUN PEPAYA UNTUK PETANI DI INDONESIA - Senjaya Machfudi Zulkif (Universitas Nahdlatul Ulama Pasuruan, 2024)
In this research, the Research and Development (R&D) method was used to produce a digital illustration book design that provides informative and interesting guidance on the production of biopesticides from papaya leaves. The book also introduces the correct method of producing biopesticides from papaya leaves using a digital illustration book medium, suitable for millennial farmers in Indonesia. The stages in the Research and Development (R&D) method, as proposed by (Sugiyono, 2015, p. 97), were carried out, which included identifying potential and problems, collecting information, product design, design validation, design improvement, product testing, design refinement, and publication. The validity testing was conducted twice by the first media expert, with validity percentages of 70% and 84%, while the second media expert achieved an 85% validity percentage. The content expert also conducted a validity test, obtaining a validity percentage of 75%. After being revised based on the validation results, the digital illustration book on papaya leaf biopesticides was piloted among millennial farmers in Indonesia. The trial results indicated that the digital illustration book was highly good or highly suitable for use, with a percentage of 95%. Keywords: Research and Development (R&D) method, Digital illustration book, Biopesticide production guide, Papaya leaves, Millennials farmers in Indonesia.